Isolation and molecular identification of wine yeasts from a Brazilian vineyard - Baffi, Milla Alves [UNESP]; Bezerra, Carolina dos Santos [UNESP]; Arevalo-Villena, Maria; Isabel Briones-Perez, Ana; Gomes, Eleni [UNESP]; Da Silva, Roberto [UNESP] (Springer, 2011)
Traditional winemaking is carried out by spontaneous yeasts from the vineyard that persist throughout the alcoholic fermentation. This study examined the diversity of yeast species isolated from grape skin and musts of two varieties of Vitis labrusca from a vineyard in the southeast region of Brazil (Jales, So Paulo), which produces artisanal wines. Molecular identification was achieved by a combination of PCR-RFLP/sequencing of the internal transcribed spacers (ITS) and sequencing of the D1/D2 domain of ribosomal DNA. Eighty yeast samples were isolated from grapes and musts, and seven different species were identified. The diversity of species varied according to the grape variety. The most frequent species were Hanseniaspora uvarum with 28 isolates, followed by Issatchenkia occientalis with 19 isolates and Issatchenkia orientalis with 16 isolates. Other species with a lower number of isolates were: Issatchenkia terricola, Saccharomyces cerevisiae, Aureobasidium pullulans and Sporidiobolus pararoseus. Our results showed that molecular identification is a very powerful identification method in which natural isolates of ascomycetous or basidiomycetous yeasts can be rapidly and reliably identified with better reproducibility and higher throughput than conventional phenotypic methods. This is the first report of the diversity of indigenous yeast species from a vineyard in Brazil.
Keywords: Yeast; Non-Saccharomyces; Brazil; Wine aroma